Inovasi Kepala Madrasah dalam Mengembangkan Kreativitas Siswa di Madrasah Ibtidaiyah Al Hudy Denpasar Tahun Pelajaran 2019/2020 - Rohmat, Muhammad Nur; Mahrusun, Mahrusun; Hisyam, Mohammad (Faidatuna, 2022)
Innovation is an idea, practice, item, event, or method that is felt or observed as something new for someone to create innovation in improving the quality of education in madrasas and developing a wide reach. This innovation can be developed through the creativity of female students to instill a spirit in every child. The aim of this research is to find out how innovative the Madrasah Head is in telling about student creativity at Madrasah Ibtidaiyah Al Hudy Denpasar for the 2019/2020 academic year, and to find out the supporting and inhibiting factors in reading student creativity at Madrasah Ibtidaiyah Al Hudy Denpasar for the 2019/2020 academic year. This type of research is descriptive with a qualitative approach with three data collection techniques, namely: observation, documentation and interviews. The results of this research are that the madrasa head's innovation in developing student creativity at MI Al Hudy has gone quite well, as evidenced by the increase in students who are interested and interested in the field of crafts and the proof of their works, as well as supporting factors in developing student creativity in MI Al Hudy provides support from the madrasa head, professional teachers, support from student parents, regular training, a supportive environment and adequate madrasa facilities. Meanwhile, the inhibiting factors are families who do not fully have the same vision and mission in developing student creativity, the negative influence of social media or technology, limited time.